2020
DOI: 10.3390/ijms22010278
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Abcc6 Transporter in Zebrafish Causes Ocular Calcification and Cardiac Fibrosis

Abstract: Pseudoxanthoma elasticum (PXE), caused by ABCC6/MRP6 mutation, is a heritable multisystem disorder in humans. The progressive clinical manifestations of PXE are accompanied by ectopic mineralization in various connective tissues. However, the pathomechanisms underlying the PXE multisystem disorder remains obscure, and effective treatment is currently available. In this study, we generated zebrafish abcc6a mutants using the transcription activator-like effector nuclease (TALEN) technique. In young adult zebrafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…Using a CRISPR/Cas9-based methodology we were able to create frameshift mutations in both functional zebrafish ABCC6 paralogs, abcc6a, and abcc6b.1. The phenotypic analysis of single and double mutants, both at larval and adult stages suggested that whereas abcc6a has major roles in mineralization, as has been suggested by previous studies (Mackay et al, 2015;Van Gils et al, 2018;Sun et al, 2021), abcc6b.1 appears to be dispensable for this process under normal conditions. In the absence of Abcc6a function we observe precocious mineralization as early as 10 dpf (Figure 2), and in adults this process leads to deformed vertebrae and ectopic mineralization foci deposited in between the vertebrae leading to a characteristic phenotype (Figure 3), reminiscent to some scoliosis models (Grimes et al, 2016).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Using a CRISPR/Cas9-based methodology we were able to create frameshift mutations in both functional zebrafish ABCC6 paralogs, abcc6a, and abcc6b.1. The phenotypic analysis of single and double mutants, both at larval and adult stages suggested that whereas abcc6a has major roles in mineralization, as has been suggested by previous studies (Mackay et al, 2015;Van Gils et al, 2018;Sun et al, 2021), abcc6b.1 appears to be dispensable for this process under normal conditions. In the absence of Abcc6a function we observe precocious mineralization as early as 10 dpf (Figure 2), and in adults this process leads to deformed vertebrae and ectopic mineralization foci deposited in between the vertebrae leading to a characteristic phenotype (Figure 3), reminiscent to some scoliosis models (Grimes et al, 2016).…”
Section: Discussionsupporting
confidence: 62%
“…Development of the Abcc6 −/− mouse models (Gorgels et al, 2005;Klement et al, 2005) resulted in fundamental discoveries related to the pathomechanism of PXE. In addition a number of attempts have been made to find or create suitable zebrafish models (Li et al, 2010;Mackay et al, 2015;Van Gils et al, 2018;Sun et al, 2021). Thanks to recent methodological developments and a number of advantageous features, the popularity of zebrafish as a pre-clinical disease model has been increasing over the past two decades (Lieschke and Currie, 2007;Varga et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With small hearts, differences in intracellular calcium cycling, and scarce fibrosis, the anticipated value of modeling structural arrhythmias and chronic cardiac fibrosis related to HF in zebrafish is limited. However, some do report significant chronic cardiac fibrosis in zebrafish ( Huang et al, 2014 ; Sun et al, 2020 ). In addition to scarcity of chronic cardiac fibrosis in zebrafish, the same applies to lack of cardiac fatty tissue, a hallmark of human arrhythmogenic CM ( Gerull and Brodehl, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the abcc6a zebrafish model develops an abnormal calcification phenotype but one that does not recapitulate the human PXE. A new zebrafish model was recently created using the transcription activator-like effector nuclease (TALEN) technique [ 115 ]. These animals displayed similar skeletal changes as well as calcification in the ocular Bruch’s membrane and a range of other previously unreported manifestations, such as cardiac fibrosis.…”
Section: Animal Modelsmentioning
confidence: 99%